Analisis Penyelesaian Sengketa Pemutusan Hubungan Kerja Secara Sepihak Oleh Pengadilan Hubungan Industrial (Studi Putusan Nomor 10/pdt.sus-PHI/2023/Pn.Tjk): Analysis Of Dispute Resolution On Unilateral Termination Of Employment Relations By The Industrial Relations Court (Decision Number 10/Pdt.Sus-Phi/2023/Pn.Tjk) - Indra Permana; Yogo Pamungkas (Reformasi Hukum Trisakti, 2025)
The settlement of industrial relations disputes in Indonesia is regulated in Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes. This study focuses on a legal analysis of the decision of the industrial relations court in Tanjungkarang in a case of termination of employment that did not go through bipartite negotiations first. The problem is the dispute resolution process is in accordance with the relevant laws, and whether the judge's considerations in the decision are in accordance with Law Number 13 of 2003 concerning Manpower. The research method used is normative legal research with a descriptive analysis research type. Data were collected through literature studies from primary, secondary, and tertiary legal materials. Data analysis was carried out qualitatively by drawing conclusions deductively. Bipartite negotiations are not a formal requirement for submitting a lawsuit to the Court, but are a formal requirement for submitting a request for mediation to a labor mediator. This research is expected to provide theoretical and practical benefits in understanding civil procedural law and the settlement of employment disputes in Indonesia.